INFLUENCIA DA DIMENSAO VERTICAL NO REGISTRO DA RELACAO CENTRAL EM DESDENTADO - Passanezi, R.; Santini, J. M. (My University, 1973)
Vertical dimensions of occlusion with no change or with a 2 mm increase were used to study centric relation records in 28 female and 14 male patients (by swallowing and extra oral graphic techniques). Each patient provided 2 record plates. Differences between apex of the Gothic arch and swallowing 'point' were measured in laterolateral and anteroposterior direction by comparator microscopy. Records of centric relations taken by both techniques and in both directions showed no significant differences when 2 mm were added to vertical dimensions. No significant differences were found between mean differences in both directions, in both sexes, with both vertical dimensions. It is concluded that this technique is a secure guide for recording centric relations. (20 references).
The influence of the vertical dimension on the record of the centric relation in edentulous people